Perspectives on Schwann-like cells derived from bone marrow-mesenchymal stem cells: Advancing peripheral nerve injury therapies - Ferreira, Lucas Vinícius de Oliveira [UNESP]; Amorim, Rogério Martins [UNESP] (Baishideng Publishing Group, 2025)
Peripheral nerve injuries are clinical conditions that often result in functional deficits, compromising patient quality of life. Given the relevance of these injuries, new treatment strategies are constantly being investigated. Although mesenchymal stem cells already demonstrate therapeutic potential due to their paracrine action, the transdifferentiation of these cells into Schwann-like cells (SLCs) represents a significant advancement in nerve injury therapy. Recent studies indicate that SLCs can mimic the functions of Schwann cells, with promising results in animal models. However, challenges remain, such as the diversity of transdifferentiation protocols and the scalability of these therapies for clinical applications. A recent study by Zou et al provided a comprehensive overview of the role of bone marrow-derived mesenchymal stem cells in the treatment of peripheral nerve injuries. Therefore, we would like to discuss and explore the use of SLCs derived from bone marrow-derived mesenchymal stem cells in more detail as a promising alternative in the field of nerve regeneration.
Keywords: Cell therapy; Nerve repair; Peripheral nervous system; Transdifferentiation; Transplantation